Two previously undescribed triterpenoid saponins from the roots and rhizomes of Caulophyllum robustum Maxim - Cong-Yu Zhang; Yu-Mei Wang; Peng-Cheng Qiu; Jia-Yu Feng; Bing-Wen Wang; Yu Cao; Yi-Sha Wei; Yi-Tong Zhou; Hai-Feng Tang; Yun-Yang Lu; Qian Zhang (Frontiers in Chemistry)
Since ancient times, plants have provided humans with important bioactive compounds for the treatment of various diseases. Nine compounds were isolated from the roots and rhizomes of Caulophyllum robustum (a plant in the family Panaxaceae), including two new saponins C. Spanion A and C. Spanion B (1-2) and seven known saponins (3-9). The cytotoxicity of these compounds on human cancer cell lines was analyzed using MTT method. Compounds 6 and 9 exhibit cytotoxicity towards these three types of human cancer cells (<10 μM). By utilizing the SEA platform for target prediction, a common tumor related target CD81 was identified. The molecular docking of saponins 1, 2, 6, and 9 with CD81 protein showed strong binding affinities ranging from -4.5 to -7.1 kcal/mol. Research has shown that these compounds can become potential anti-tumor drugs. Further research is still recommended to understand its exact molecular mechanism and toxicological effects.